Developing the African national health research systems barometer. Issue 1 (December 2016) - Kirigia, Joses; Ota, Martin; Senkubuge, Flavia; Wiysonge, Charles; Mayosi, Bongani
Abstract Background A functional national health research system (NHRS) is crucial in strengthening a country's health system to promote, restore and maintain the health status of its population. Progress towards the goal of universal health coverage in the post-2015 sustainable development agenda will be difficult for African countries without strengthening of their NHRS to yield the required evidence for decision-making. This study aims to develop a barometer to facilitate monitoring of the development and performance of NHRSs in the African Region of WHO. Methods The African national health research systems barometer algorithm was developed in response to a recommendation of the African Advisory Committee for Health Research and Development of WHO. Survey data collected from all the 47 Member States in the WHO African Region using a questionnaire were entered into an Excel spreadsheet and analysed. The barometer scores for each country were calculated and the performance interpreted according to a set of values ranging from 0% to 100%. Results The overall NHRS barometer score for the African Region was 42%, which is below the average of 50%. Among the 47 countries, the average NHRS performance was less than 20% in 10 countries, 20–40% in 11 countries, 41–60% in 16 countries, 61–80% in nine countries, and over 80% in one country. The performance of NHRSs in 30 (64%) countries was below 50%. Conclusion An African NHRS barometer with four functions and 17 sub-functions was developed to identify the gaps in and facilitate monitoring of NHRS development and performance. The NHRS scores for the individual sub-functions can guide policymakers to locate sources of poor performance and to design interventions to address them.